Fiber burden and asbestos-related diseases: an umbrella review - José María Ramada Rodilla; Beatriz Calvo Cerrada; Consol Serra Pujadas; George L. Delclos; Fernando G. Benavides (Elsevier, 2022)
Objective: What are the levels of asbestos exposure that cause each type of health effect? The objective of this study was to review the available scientific evidence on exposure levels for asbestos and their relationship to health effects. Method: An umbrella review of English-language reviews and meta-analyses, from 1980 to March 2021 was conducted. We included reviews involving quantified asbestos exposures and health outcomes. The review has been adapted to the indications of the PRISMA declaration. Methodological quality of the selected studies was assessed using the AMSTAR instrument. Results: We retrieved 196 references. After applying the search strategy and quality analysis, 10 reviews were selected for in-depth analysis. For lung cancer, the highest risk was observed with exposure to amphiboles. Longer, thinner fibers had the greatest capacity to cause lung cancer, especially those > 10 μm in length. For mesothelioma, longer and thinner fibers were also more pathogenic; amphiboles ≥ 5 μm are especially associated with increased mesothelioma risk. No studies observed an increased risk for lung cancer or mesothelioma at asbestos exposure levels < 0.1 f/ml. No reviews provided information on exposure concentrations for pulmonary fibrosis. Currently, there is limited evidence in humans to establish the causal relationship between gastrointestinal cancer and asbestos exposure. Conclusions: Banning all asbestos exposure remains the best measure to preventing its negative health effects. The highest quality reviews and meta-analyses support that there is little risk of lung cancer or mesothelioma at daily exposure levels below 0.1 f/ml. Resumen: Objetivo: Revisar la evidencia científica disponible sobre los niveles de exposición al asbesto y su relación con los efectos sobre la salud. Método: Se realizó una revisión de revisiones sistemáticas y metaanálisis en inglés, desde 1980 hasta marzo de 2021. Se incluyeron revisiones que involucran exposiciones cuantificadas al asbesto y resultados de salud. La revisión se adaptó a las indicaciones de la Declaración PRISMA. La calidad metodológica de los estudios seleccionados fue evaluada mediante el instrumento AMSTAR. Resultados: Se recuperaron 196 referencias y tras aplicar la estrategia de búsqueda y analizar la calidad se seleccionaron 10 revisiones para un análisis en profundidad. Para el cáncer de pulmón, se observó mayor riesgo con la exposición a anfíboles. Las fibras más largas y delgadas presentaron mayor capacidad de causar cáncer de pulmón, especialmente aquellas de longitud > 10 μm. Para el mesotelioma, las fibras más largas y delgadas también fueron más patógenas; los anfíboles ≥ 5 μm se asociaron con un mayor riesgo de mesotelioma. Ningún estudio observó mayor riesgo de cáncer de pulmón o de mesotelioma con niveles de exposición al asbesto < 0,1 f/ml. Ningún estudio proporcionó información sobre concentraciones de exposición para la fibrosis pulmonar. Actualmente existe evidencia limitada en humanos para establecer la relación causal entre la exposición al asbesto y el cáncer gastrointestinal. Conclusiones: Prohibir toda exposición al asbesto es la mejor medida para prevenir sus efectos negativos para la salud. Las revisiones y metaanálisis de más alta calidad respaldan que hay escaso riesgo de cáncer de pulmón y de mesotelioma con niveles de exposición diaria por debajo de 0,1 f/ml.